Muscle synergies after stroke are correlated with perilesional high gamma. Issue 12 (21st October 2016) - Godlove, Jason; Gulati, Tanuj; Dichter, Ben; Chang, Edward; Ganguly, Karunesh
Abstract: Movements can be factored into modules termed "muscle synergies". After stroke, abnormal synergies are linked to impaired movements; however, their neural basis is not understood. In a single subject, we examined how electrocorticography signals from the perilesional cortex were associated with synergies. The measured synergies contained a mix of both normal and abnormal patterns and were remarkably similar to those described in past work. Interestingly, we found that both normal and abnormal synergies were correlated with perilesional high gamma. Given the link between high gamma and cortical spiking, our results suggest that perilesional spiking may organize synergies after stroke.